Fishermen's Satisfaction with Fisheries Extension Activities in Padang Pariaman Regency, West Sumatra Province - Rindi Metalisa; Zulkarnain Zulkarnain; Mahrunnisa Mahrunnisa; Chicka Willy Yanti (Berkala Perikanan Terubuk, 2023)
Fisheries counseling activities are an asset in realizing independent, competitive, and resilient fishermen in Padang Pariaman regency. Fishermen have hopes and goals to develop their businesses, so they participate in fisheries extension activities. This study examines fishermen's satisfaction with fisheries extension activities in Padang Pariaman Regency, West Sumatra. The research implementation starts from June to October 2022. The research uses a survey method with an explanatory research approach. Respondents were taken based on the accidental sampling technique using the Slovin Formula, so the number of respondents used was 68 fishermen. This study uses descriptive analysis data. Fishermen's satisfaction in fisheries counseling activities is still felt to have yet to satisfy fishermen. Fishermen's satisfaction in fisheries extension activities consists of three stages of activity, namely: 1) Fishermen feel dissatisfied at the extension planning stage;  2) the implementation of fisheries counseling activities are in the dissatisfied category; 3) the evaluation of fisheries extension activities is in the dissatisfied category